Nav1.7 expression is increased in painful human dental pulp - Levinson S Rock; Perry Griffin M; Luo Songjiang; Henry Michael A (SAGE Publishing, 2008)
Abstract Background Animal studies and a few human studies have shown a change in sodium channel (NaCh) expression after inflammatory lesions, and this change is implicated in the generation of pain states. We are using the extracted human tooth as a model system to study peripheral pain mechanisms and here examine the expression of the Nav1.7 NaCh isoform in normal and painful samples. Pulpal sections were labeled with antibodies against: 1) Nav1.7, N52 and PGP9.5, and 2) Nav1.7, caspr (a paranodal protein used to identify nodes of Ranvier), and myelin basic protein (MBP), and a z-series of optically-sectioned images were obtained with the confocal microscope. Nav1.7-immunofluorescence was quantified in N52/PGP9.5-identified nerve fibers with NIH ImageJ software, while Nav1.7 expression in myelinated fibers at caspr-identified nodal sites was evaluated and further characterized as either typical or atypical as based on caspr-relationships. Results Results show a significant increase in nerve area with Nav1.7 expression within coronal and radicular fiber bundles and increased expression at typical and atypical caspr-identified nodal sites in painful samples. Painful samples also showed an augmentation of Nav1.7 within localized areas that lacked MBP, including those associated with atypical caspr-identified sites, thus identifying NaCh remodeling within demyelinating axons as the basis for a possible pulpal pain mechanism. Conclusion This study identifies the increased axonal expression and augmentation of Nav1.7 at intact and remodeling/demyelinating nodes within the painful human dental pulp where these changes may contribute to constant, increased evoked and spontaneous pain responses that characterize the pain associated with toothache.